An indirect heating solution to reduce CO₂ emission and improve efficiency of gas distribution networks - Stefan Romocki; Jamshid Zarkesh; Henry Melloy; Ivan Cheung; Sébastien Le Fouest (Energy Reports, 2018)
The gas industry relies on indirect heating to prevent gas from freezing when it is transferred from high-pressure networks to lower pressure distribution systems. The main challenge in preheating natural gas is designing an indirect heating system capable of consistently maintaining a target temperature, despite large load diversity. The most common form of heating technology has traditionally been water bath heaters and boiler houses. In this paper, a novel technology is introduced, and its performance compared to existing installations. The Immersion Tube Thermosyphon Heater was developed specifically to address high load diversity; it combines a high-efficiency immersion burner with a sub-atmospheric two-phase loop thermosyphon. The use of low-temperature steam provides a flexible and precise solution for temperature control easily adapted to variable gas flows. The Immersion Tube Thermosyphon achieved an average thermal efficiency of 90%, considerably higher than the 46% efficient water bath, allowing an estimated annual saving of 7,660 tonnes CO2 for 1-megawatt gross heat capacity operating with a 50% load factor.
Keywords: 330; Gas preheating; Load diversity; Temperature control; Thermal efficiency; Transient load; Two-phase loop thermosyphon; Water bath heaters